Tinjauan Hukum Islam terhadap Uang Panai’ dalam Tradisi Pernikahan Suku Bugis-Makassar - Zahrum N.; Anita Marwing (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This study aims to find out the views of Islamic law regarding the tradition of giving Uang Panai’ in Bugis weddings. This study uses a normative juridical approach (library research). The results of this study indicate that Uang Panai’ and Mahar in the tradition of the Bugis-Makassar community are an inseparable unit in marriage. If a man wants to propose to a woman, it is obligatory for him to provide a dowry along with the Panai’ money. Because Uang Panai’ is intended as a wedding fee without which the marriage process will be canceled. In Islam, the law of giving Uang Panai’ as a form of walīmah (wedding reception costs) is permissible (mubah). However, in this case, walīmah activities in Islamic law should not be carried out excessively, even to the point of burdening the men. If, burdening the male party, this tradition has violated Islamic law because it has made it difficult to carry out a marriage. Therefore, giving Uang Panai’ is a form of wata'awmanu alal birri (and please help you in doing good deeds) because it really helps the woman's family carry out the wedding ceremony. The conclusion of this study is that the giving of Uang Panai’ in a Makassar Bugis marriage is permissible if it is not excessive and does not conflict with the Qur'an and Hadith.